2016
DOI: 10.1002/wcm.2698
|View full text |Cite
|
Sign up to set email alerts
|

Distributed trigger counting algorithms for arbitrary network topology

Abstract: The distributed trigger counting (DTC) problem is a fundamental block for many distributed applications. Particularly, such a problem is to raise an alert while the number of triggers received by the whole system reaches a pre‐defined amount. There have been a few algorithms proposed to solve the DTC problem in the literature. However, these existing algorithms are all under the assumption that each process knows what kind of network topology the whole system forms as well as playing distinct kind of role in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Chang et al proposed a DTC algorithm without any assumption about the network topology [5]. The algorithm they propose primarily focuses on sensor networks whose network topology is unknown ahead of time.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Chang et al proposed a DTC algorithm without any assumption about the network topology [5]. The algorithm they propose primarily focuses on sensor networks whose network topology is unknown ahead of time.…”
Section: Related Workmentioning
confidence: 99%
“…Only the case where the number of triggers is significantly greater than the number of nodes, i.e., w n, is taken into account. Otherwise, the DTC problem can be solved with O(n) messages [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al proposed a DTC algorithm for arbitrary network topology [ 19 ]. The algorithm they proposed is mainly focused on wireless sensor networks (WSNs) in which network topology cannot be known in advance.…”
Section: Related Workmentioning
confidence: 99%
“…Emek et al improved lower bounds on DTC algorithms and proposed the probabilistic DTC algorithm, where its message complexity is low but MaxRcvLoad is not bounded [ 18 ]. Chang et al suggested the DTC algorithm that can work with any network topology [ 19 ].…”
Section: Introductionmentioning
confidence: 99%